From triumph to disaster : the fatal flaws of German generalship from Moltke to Guderian - Macksey, Kenneth (Mechanicsburg, PA : Stackpole Books, 1996)
"The mighty German armed forces have twice this century been forced from the brink of victory to defeat. Was this inevitable, given their structure, leadership and history?" "Kenneth Macksey examines the inherent flaws in the German military system and its generalship, focusing on the two World Wars but also taking into account major preceding events such as the Seven Years' War, the Napoleonic Wars and the Danish, Austrian and Franco-Prussian wars. A nation that traditionally had to struggle to survive in territory with few natural defensive boundaries, Germany developed an aggressive and arrogant outlook, which led it via initial successes in the 1860s and 1870s to dreams of world domination, causing overstretch and disaster." "Macksey highlights the German military's tendency to underestimate the enemy and believe its own propaganda; its failure to adopt a war policy far-reaching enough to sustain anything other than short wars; the immense political power wielded by the military staffs; and many other factors that history has shown damaged Germany's chances of success in war. Set against these flaws was the brilliance of individual generals and military thinkers, the innovative development of the military forces, and the skill and tenacity of the men who did the fighting. Macksey inspects the reasons for the actions of the great German commanders - including Scharnhorst, Clausewitz, Moltke, Hindenburg, Ludendorff, Kesselring, Guderian, Rommel, Manstein and many others, as well as their Kaisers and, of course, Adolf Hitler."--BOOK JACKET.
Includes bibliographical references (pages 230-232) and index.
Keywords: 1800-1999; Leadership -- History -- 19th century